Type 2 diabetes: prevalence and associated factors in a Brazilian community – the Bambuí health and aging study - Passos, Valéria Maria de Azeredo; Barreto, Sandhi Maria; Diniz, Leonardo Maurício; Lima-Costa, Maria Fernanda (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Diabetes is an in- creasing cause of death in developing countries. Our objective was to describe the prevalence and clinical factors associated with diabetes and impaired fasting glycemia among adults (18-59 years) and elderly adults (60+ years). DESIGN AND SETTING: Population based, cross- sectional study in Bambuí, Brazil. METHODS: 816 adult and 1,494 elderly partici- pants were interviewed; weight, height and blood pressure measured; and blood samples collected. Diabetes was deﬁned as plasma fasting glucose ≥126 mg/dl and/or use of hypoglycemic agents; impaired fasting glycemia as glycemia of 110- 125 mg/dl. Associations were investigated using multinomial logistical regression (reference: fasting glycemia ≤109 mg/dl). RESULTS: Among the elderly, 218 (14.59%) presented diabetes and 199 (13.32%) impaired fasting glycemia, whereas adult prevalences were 2.33% and 5.64%. After multinomial analysis, diabetes remained associated, for adults, with increased waist-to-hip ratio and total cholesterol ≥ 240 mg/dl; for elderly adults, with family history of diabetes, body-mass index of 25-29 kg/m2, body-mass index ≥30 kg/m2, increased waist-to-hip ratio, low HDL-choles- terol triglyceridemia of 200-499 mg/dl and triglyceridemia ≥ 500 mg/dl. Among adults, impaired fasting glycemia remained associated negatively with male sex and positively with ages of 40-59 years, physical inactivity and increased waist-to-hip ratio; among the elderly, with alcohol consumption, overweight, obesity and triglycerides > 200 mg/dl. CONCLUSIONS: The results reinforce the importance of interventions to reduce physical inactivity, alcohol consumption, obesity and dyslipidemia, so as to prevent increasing inci- dence of diabetes.